Economic valuation of integrated pest management among rice farmers of Muda Agricultural Development Authority, Malaysia - Mohd Amir, Hairuddin (2012)
Concerns over the impact of pesticide use have prompted Malaysia and other countries to develop a program of integrated pest management (IPM) which seeks to address the effects of excessive use of pesticides. The program is beneficial to the communities at large and can be measured in economic terms. The benefits include improvements in food safety, water quality, pesticide application safety, and long run sustainability of pest management systems. This study aims to investigate the health and environment benefits of the IPM practices in paddy (Oryza sativa) cultivation. Primary data were collected from 454 paddy farmers in four regions of the Muda Agricultural Development Authority (MADA) located in the states of Kedah and Perlis. The survey which included areas in Kuala Perlis as Region 1, Kuala Jitra (Region 2), Pendang (Region 3) and Kota Sarang Semut (Region 4) was undertaken to identify farm and farmer characteristics, pesticide usage, pest management practices, awareness and perceptions about pesticide hazards, and willingness to adopt specific IPM technologies. A double bounded dichotomous choice of contingent valuation approach survey was used to evaluate farmers’ choice of willingness-to-pay (WTP) to avoid risks of pesticide use in different environmental categories namely human, beneficial insects, aquatic species, avian, and livestocks. The adoption rates for each of the IPM technologies, were predicted as follows: 97.8% for agronomic practices, 59.91% for complementary weed control strategies, 55.29% for biological control, 54.85% for the optimal use of pesticides, and 30.40% for economic threshold level. A contingent valuation survey approach to reduce pesticide risks by their “bids” on various price of “safer pesticide” each category were RM 170.01 for human safety, RM 164.58 for animal safety, RM 161.24 for aquatic safety, RM 160.96 for beneficial insect’s safety and RM 158.66 for avian safety. Combining WTP bids each farmers and the risks percentage reduction/avoided, the benefits of the IPM adoption for one paddy season were estimated to total RM442.76. The aggregate environmental benefits to the paddy community in MADA, Malaysia (454 farmer in four region) totalled RM201,014. On top of the benefits in environmental value, the reduction in pesticide use also reduced operating expenses. Calculated aggregate cost savings per season were RM756,393 for insecticides, RM40,537 for fungicides and RM94,753 for herbicides. The cost savings of the IPM practices to 454 farmers in the four regions amounted to RM 891,683 per season. The results of this study can contribute to a better targeting of health policies and design of IPM programmes aiming to reduce negative effects of excessive pesticide use.